2021
DOI: 10.1155/2021/9953545
|View full text |Cite
|
Sign up to set email alerts
|

Tunisian Pistachio Hull Extracts: Phytochemical Content, Antioxidant Activity, and Foodborne Pathogen Inhibition

Abstract: The present study aimed to discriminate pistachio (Pistacia vera L.) hulls belonging to three different Tunisian geographical origins and extracted separately by hexane, acetone, acetonitrile, and water in terms of phytochemicals and antioxidant and antibacterial activities using multivariate analysis. Significant differences ( P < 0.05 ) in the phytochemical content, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In addition, differences between the three different kinds of T. officinale extracts were perceived by using a heat map which displayed high (red color) to low (green color) activities vividly ( Figure 3(d) ). Previously, Elhadef et al [ 51 ] and Fernández-Poyatos et al [ 52 ] also used a heat map to discriminate between different species and to observe the contribution of each extract to the biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences between the three different kinds of T. officinale extracts were perceived by using a heat map which displayed high (red color) to low (green color) activities vividly ( Figure 3(d) ). Previously, Elhadef et al [ 51 ] and Fernández-Poyatos et al [ 52 ] also used a heat map to discriminate between different species and to observe the contribution of each extract to the biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that phenolic chemicals found in the aqueous extract of pistachio hull have an inhibitory effect on a number of food-borne bacteria. In addition, the phenolics, flavonoid, and anthocyanin compounds were strongly associated with antibacterial activity 51 . Pistachio hull contain phenolic compounds that are rich in hydroxybenzoic acids (vanillic and gallic acids), flavonoids (catechins, quercetin, and apigenin), and tannins 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Two Gram-negative bacteria— E. coli ATCC 8739 and S. enterica Typhimurium ATCC 14028—and two Gram-positive bacteria— S. aureus ATCC 6538 and L. monocytogenes ATCC 19117—from the collection of the Laboratory of Microbial Biotechnology, Enzymes, and Biomolecules (LMBEB), Center of Biotechnology of Sfax (CBS), Tunisia, were used to investigate the antibacterial potential of the selected oxygenated monoterpenes. Bacterial cultures were prepared in a Luria–Bertani (LB) agar medium and incubated overnight at 37 °C according to the method reported by Elhadef et al [ 21 ].…”
Section: Methodsmentioning
confidence: 99%